Anti-intra Ocular Pressure of Stachytarpheta jamaicensis Leaf Aqueous Extract on Prednisolone-Induced intra Ocular Pressure in Rabbits - Odjimogho, Stella E.; Idu, MacDonald; Odjimogho, Sunny E.; Gabriel, Benjamin O. (African Journal of Sciences and Traditional Medicine, 2025)
Intraocular pressure is generated by the dynamics of secretion and outflow of aqueous humour, a transparent colorless fluid (secretion) that fills the complex space in the front part of the eye. This study is aimed at investigating the effect of Stachytarpheta jamaicensi leaf aqueous extract on induced intraocular pressure (IOP) in rabbits to validate its ocular potential. The experiment involved twenty five (25) healthy adult rabbits (n=5), divided into negative positive and positive control (0.5% timolol), and the treatment groups (SJ) at graded concentrations (0.00351, 0.00702 and 0.0143 mg/ml).The baseline IOP value of all rabbits were measured with Perkins hand-held applanation tonometer before the commencement of the study. Thereafter, the IOP of the experimental and treatment groups were induced with daily instillation of 1% prednisolone suspension for one week until IOP reading was 5 mm. Hg above the baseline level. The treatment groups were administered with varying concentrations of the aqueous extract of Stachytarpheta jamaicensis. The IOP was also measured at intervals before each application of aqueous extract until the IOP returned to baseline level. The result showed the distribution of the mean IOP before, and after instillation with 1% Prednisolone suspension and the treatment with varying concentrations of S. jamaicensis extract. The observed mean IOP before and after the treatment with prednisolone was 8.77±0.5 mmHg, and 14.2±0.51 mmHg respectively. After oral application of S. jamaicensis extract had a significant mean IOP decrease across the days when compared with the controls. The decrease in mean IOP was observed with a significant increase at higher concentrations of the extract, hence the plant caused a reduction in IOP level. Inconclusion, the plants have been implicated in reducing intraocular pressure in rabbits, thus may be helpful in the management of intraocular pressure (IOP), thereby, required further study to validate the efficacy of the extract.